2018
DOI: 10.1002/ece3.3749
|View full text |Cite
|
Sign up to set email alerts
|

Random species loss underestimates dilution effects of host diversity on foliar fungal diseases under fertilization

Abstract: With increasing attention being paid to the consequences of global biodiversity losses, several recent studies have demonstrated that realistic species losses can have larger impacts than random species losses on community productivity and resilience. However, little is known about the effects of the order in which species are lost on biodiversity–disease relationships. Using a multiyear nitrogen addition and artificial warming experiment in natural assemblages of alpine meadow vegetation on the Qinghai‐Tibeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…[37,38]). Although the use of randomized species combinations offers valuable mechanistic insights [39], incorporation of realistic patterns in community assembly/disassembly is essential for identifying the effects of current and forecasted biodiversity changes [40]. By sampling 147 wetlands over a 6-year period, we found that one or two compositions typically accounted for 65 -100% of field observations for each richness level, with many potential combinations either rare or unobserved.…”
Section: Discussionmentioning
confidence: 91%
“…[37,38]). Although the use of randomized species combinations offers valuable mechanistic insights [39], incorporation of realistic patterns in community assembly/disassembly is essential for identifying the effects of current and forecasted biodiversity changes [40]. By sampling 147 wetlands over a 6-year period, we found that one or two compositions typically accounted for 65 -100% of field observations for each richness level, with many potential combinations either rare or unobserved.…”
Section: Discussionmentioning
confidence: 91%
“…2003 did not control for compositional change but showed that ‘disease proneness’ was an important driver of infection and Liu et al . (2018) showed that nitrogen favors disease prone plants (but see Welsh et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, such predictable changes are not expected 50 over natural biodiversity gradients (Table 1). 51 While many studies focus on measuring the diversity of host species in the context of 52 hosts (Liu et al 2018), dilution was not observed in communities that were disassembled 85 randomly, but when communities disassembled naturally, biodiversity significantly reduced 86 disease, lending further support to this hypothesis. Consequently, theory suggests that 87 biodiversity gradients associated with biodiversity loss should result in dilution effects.…”
Section: Introductionmentioning
confidence: 95%
“…Several recent studies provide a 40 promising framework for resolving this debate, suggesting that changes in the structure of 41 host communities, rather than biodiversity per se, can explain when a dilution effect should 42 be observed (Johnson et al 2013(Johnson et al , 2019Joseph et al 2013;Mihaljevic et al 2014;Strauss et 43 al. 2016;Liu et al 2018;. Implicit in these studies is a focus on 44 biodiversity loss: the structure of host communities often shifts predictably when biodiversity 45 is lost or recovered, particularly following disturbances, and often in a way that favors 46 species with combinations of physiological traits associated with increased disease risk 47 suggest that there should be a strong relationship between biodiversity and disease risk 49 following a loss of native biodiversity.…”
Section: Introductionmentioning
confidence: 99%